Sistem Fisika Keperawatan untuk Meningkatkan Pelayanan Kesehatan - Nadin Citra Fadhilah; Puput Nur Aliva; Revalina Febriayanti; Qoriah Dwi Nur Dintan; Nadia Budi Agustina; Liss Dyah Dewi Arini (Nursing Applied Journal, 2025)
Physics plays a major role in the world of health, including nursing. Various processes in nursing apply and consider the principles of physics to ensure the efficiency and effectiveness of nursing actions, the validity of measurement results and patient safety. Knowledge of physics is also used to help understand the conditions and situations faced. The use of physics in the world of health affects two important aspects, namely physiology, pathophysiology and therapy. Physiological physics can explain the function of the human body and related conditions, both in healthy and sick conditions. In terms of therapy, knowledge of physics is used in many aids used for diagnosis, healing and rehabilitation of patients. The material to be discussed below includes biomechanics, biooptics, bioacoustics and thermodynamics. These topics are some of the other topics that will be related and encountered in the nursing care process.